(untitled) (SigMe, 2024)
Cardiovascular diseases (CVD) are associated with numerous risk factors -hypertension, hypercholesterolemia, among others. An effective way to prevent CVD is to promote a healthy lifestyle. The objective of this work was to evaluate the evolution of cardiovascular risk (CVR), risk factors and lifestyle in adult patients of a private sanatorium after a healthy lifestyle promotion strategy. A prospective study was carried out. The patients spontaneously attended an initial medical consultation and 15 months later were scheduled for a re-evaluation. During that period, messages promoting a healthy lifestyle were sent. A trend to decrease in the proportion of patients with high and very high CVR was observed. No changes were recorded in the proportion of patients included in the hypertension and borderline blood pressure categories, however the mean systolic blood pressure decreased significantly. The number of patients with impaired fasting blood glucose remained constant. The proportion of subjects with hypertriglyceridemia, hypercholesterolemia, increased LDL-C, and low HDL-C levels remained constant. The number of individuals who did not reach the goal for non-HDL-C decreased. The proportion of overweight patients and with abdominal obesity were high and remained constant. No changes were recorded in the number of new smokers. Low consumption of fruits and vegetables, low physical activity, disturbed sleep and presence of some psychosocial risk factors were evident. We highlight the importance of promoting healthy LS habits due to their cardiovascular and metabolic protective role.